2011
DOI: 10.1080/09583157.2011.625397
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofMetarhizium brunneum(Hypocreales: Clavicipitaceae) on pre-imaginalRhagoletis indifferens(Diptera: Tephritidae) within and on the surface of orchard soil

Abstract: When last instar laboratory-reared Rhagoletis indifferens were allowed to pupate within non-sterile orchard soil containing incorporated Metarhizium brunneum isolate F52 conidia, a dose-related proportion died from developmental abnormalities and mycosis. When larvae entered soil superficially treated with M. brunneum, over 80% of the pupae died of developmental abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
1
1
1
Order By: Relevance
“…Pathogenicity can vary between fungal species, strains, and even isolates [62]. For example, screening conducted against peach fruit fly (B. zonata) and Oriental fruit fly (B. dorsalis) demonstrated that B. bassiana was more effective compared to Metarhizium isolates tested [35,40], which differs from our findings on Queensland fruit fly.…”
Section: Plos Onecontrasting
confidence: 91%
See 2 more Smart Citations
“…Pathogenicity can vary between fungal species, strains, and even isolates [62]. For example, screening conducted against peach fruit fly (B. zonata) and Oriental fruit fly (B. dorsalis) demonstrated that B. bassiana was more effective compared to Metarhizium isolates tested [35,40], which differs from our findings on Queensland fruit fly.…”
Section: Plos Onecontrasting
confidence: 91%
“…Thus, we also tested the susceptibility of different age groups in order to better understand when infection can occur. Pre-pupating third-instar larvae were the most susceptible soil-dwelling life stage to entomopathogenic fungi, which is consistent with what has been observed in other tephritid fruit fly species [30,35,40,62,63]. Our findings showed that one-day old pupae were comparatively less susceptible than larvae but were nonetheless vulnerable.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Si bien M. anisopliae no se registró en el presente estudio esta especie fue la más estudiada para el control de "moscas de la fruta" en la bibliografía consultada. La patogenicidad de los hongos entomopatógenos ha sido reportada para larvas de las siguientes especies de "moscas de la fruta": A. fraterculus (Rodrigues Destéfano et al, 2005;Bechara et al, 2011), A. ludens (Lezama-Gutiérrez et al, 2000;de la Rosa et al, 2002;Gandarilla-Pacheco et al ,2012), C. capitata (Ekesi et al, 2002;Ekesi et al, 2005;Quesada-Moraga et al, 2006Mochi et al, 2006;Boudjelida y Soltani, 2011;Garrido-Jurado et al, 2011a,b;Imoulan y Elmeziane, 2013), C. rosa (Ekesi et al, 2002), B. dorsalis (Aemprapa, 2007), R. indifferens (Cossentine et al, 2010(Cossentine et al, , 2011 y R. cerasi (Daniel y Wyss, 2009). En cuanto a estudios de patogenicidad realizados sobre pupas de "moscas de la fruta", la especie de tefrítido más estudiada fue C.…”
Section: Prospección De Hongos Entomopatógenosunclassified